Penerapan Metode Waterfall Pada Sistem Informasi Pendaftaran Pasien Rawat Jalan Berbasis Web Mobile - Harma Oktafia Lingga Wijaya (ISB Atma Luhur, 2017)
When the researchers conducted studies Implementation Method Waterfall In Registration Information System Web-Based Outpatient Mobile, researchers found that the health center belongs to the municipality located in the village of Lubuk Tanjung Lubuk Linggau felt the need for development in line with increased demand for health services for the community. PHC Tanjung Lubuk Housing is in the process of registration of outpatients manuallyor still use conventional manner, includes data recording the identity of the patient, make a list of queues, search medical records of patients, as well as card making patients. When enrollment of patients when treatment would still be written in a ledger and patient data and data ever experienced disease (medical records) was recorded in the general ledger and certain records and stored in a special file. This often times lead to errors and writing the name of the same patient when treated umpteenth time and the difficulty in grouping the data requires considerable time as well as the lack of assurance of data security. If we want to find the patient data needed to be looking in the archives of books one by one to determine such data. With the support of information technology, manual processing in the clinic can be replaced using a computer. In addition to fast and easy with the information system has been made of data processing has also become more accurate. The method used in the information system of registration of outpatient-based mobile web in BPS town Lubuklinggau this, and to know the running system, using a structured approach using several tools like Uml, use case diagrams, activity, sequence diagram, class diagram , while for the system development method using a sequential linear or often called